The Evolution of Galaxies 2003
DOI: 10.1007/978-94-017-3315-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Non-Standard Structure Formation Scenarios

Abstract: Abstract. Observations on galactic scales seem to be in contradiction with recent high resolution N -body simulations. This so-called cold dark matter (CDM) crisis has been addressed in several ways, ranging from a change in fundamental physics by introducing self-interacting cold dark matter particles to a tuning of complex astrophysical processes such as global and/or local feedback. All these efforts attempt to soften density profiles and reduce the abundance of satellites in simulated galaxy halos. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…This result is in agreement with findings of Knebe et al (2001) who reported systematically lower spins for halos in the WDM models with higher filtering mass. We showed that the addition of initial thermal velocities resulted in even lower spins in the WDM halos as well as a significantly larger misaligned (negative j) mass fraction.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result is in agreement with findings of Knebe et al (2001) who reported systematically lower spins for halos in the WDM models with higher filtering mass. We showed that the addition of initial thermal velocities resulted in even lower spins in the WDM halos as well as a significantly larger misaligned (negative j) mass fraction.…”
Section: Discussionsupporting
confidence: 83%
“…It was shown that WDM does help to alleviate problems of CDM with halo density profiles and, possibly, the spatial distribution of dwarf galaxies (Peebles 2001). In addition, Knebe et al (2001) compared specific angular momentum distribution in CDM halos to that of the halos formed in WDM cosmology and found no systematic difference. However, they studied halos with masses much higher than the filtering mass of the simulation and neglected the thermal velocities of the WDM particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our assumption is based on the HDM cosmology (see x 1) and on the fact that filaments are generic 7 and have similar characteristics in hot dark matter ( HDM ) and CDM scenarios ( Knebe 2003;Knebe et al 2002;Bode et al 2001). For instance, neutrinos are known to collapse into sheets and filaments in HDM simulations.…”
Section: Model Applicationmentioning
confidence: 99%
“…Without resorting to cold dark matter (CDM ), the modified Newtonian dynamics ( MOND) paradigm ( Milgrom 1983;Bekenstein & Milgrom 1984) is known to reproduce galaxy scaling relations like the Tully-Fisher relation ( Tully & Fisher 1977), the Faber-Jackson law ( Faber & Jackson 1976), and the fundamental plane ( Djorgovski & Davis 1987) as well as the rotation curves of individual galaxies over five decades in mass (Sanders & McGaugh 2002;Bekenstein 2006;Sanders & Noordermeer 2007;Milgrom & Sanders 2007, 2003Nipoti et al 2007;Famaey et al 2007a). In particular, the recent kinematic analysis of tidal dwarf galaxies by Bournaud et al (2007) is very hard to explain within the classical CDM framework, while it is in accordance with MOND Milgrom 2007).…”
Section: Introductionmentioning
confidence: 99%